The Effect of Combination of Phosphate Solubilizing Microbes, Organic Pellet Fertilizers and Inorganic Fertilizers on Nutrient Uptake of Maize Plants - Jayadi, Muhammad; Rahmadi, Rahmadi; Laban, Sartika; Nurhikmayani, Risky (Hasanuddin University, 2023)
The low uptake of N and P nutrients by maize plants can be caused by the low availability or levels of N and P nutrients in the soil used as the planting medium. The Alfisol soil used in the study had N-total levels of 0.15% (low) and P2O5 of 12.76 ppm (medium). The addition of phosphate solubilizing microbes, pelleted organic fertilizer, and inorganic fertilizer can increase the availability of N and P nutrients in the soil, so that plant uptake of N and P nutrients can also increase. This study aims to determine the effect of a combination of phosphate-solubilizing microbes (PSM), pelleted organic fertilizer, and inorganic fertilizer on the nutrient uptake of maize plants. This research was conducted at the Experimental Farm, Faculty of Agriculture, Hasanuddin University and plant samples were analyzed at Hasanuddin University's Soil Fertility Chemistry Laboratory, Department of Soil Science, Faculty of Agriculture. This study used a Randomised Group Design (RGD). The treatments consisted of a combination of M0 = without phosphate solubilizing microbes; M1 = addition of phosphate solubilizing microbes; B0 = without pelleted organic fertilizer; B1 = pelleted organic fertilizer dose of 5 tonnes/ha; B2 = pelleted organic fertilizer dose of 10 tonnes/ha; A0 = without inorganic fertilizer; A1 = inorganic fertilizer 50% of the recommended dose. The results showed that the M0B2A0 treatment produced plants with the highest level of N nutrient uptake, which was 633.33% higher than the M0B0A0 treatment. In comparison, the M1B2A1 treatment had plants with the highest level of P nutrient uptake, which was 933.33% higher than the M0B0A0 treatment.